The torrents of spring : a romantic novel in honor of the passing of a great race - Hemingway, Ernest, 1899-1961.; Arrow Books (London : Arrow Books, 2006)
Reprint of a 1926 satirical romance about Scripps O'Neil, a fickle young man who marries one woman and instantly wants another, and Yogi Johnson, a war veteran whose brief fling with a Parisian woman has left him unable to love.
Young Adult
Keywords: Man-woman relationships -- United States -- Fiction; Man-woman relationship -- Fiction; United States -- Social life and customs -- Fiction